Remarks at the Annual Conference on Development Economics - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed that it is crucial to have economic growth and it is crucial to adhere to policies which are tried and true in terms of balance, in terms of equilibrium, in terms of monetary, and fiscal policy. The real issues are how can one deal with poverty within the framework of environmental sustainability, with inclusive and sustainable programs, with participation, and with results that can make a big enough difference. In the last seven years there has been a fantastic change in the weighting between the net flow of funds from the official institutions compared with the private sector—to the point where today private sector flows are six times official flows. The Bank is trying to deal with these new interfaces: working with the clients in a more responsive and less dogmatic fashion; asking how one can differentiate between economies; building a knowledge bank so that the Bank can leverage knowledge as a key driver of development.